"Jokes are the hardest thing to translate": parodying history and nationhood in contemporary Southeast Asian Novels - Karunungan, Patricia (Nanyang Technological University, 2020)
Although postcolonial fictions may be classified under modernism and postmodernism for their subversive uses of language, a marked absence of technical innovation seems to persist in anglophone Southeast Asian novels. However, it is more accurate to say that little critical attention has thus far been paid to their narratology, as the region’s literature has conventionally been valued for its representations of history and politics rather than how these representations are achieved. The novels Ilustrado (2008) by Miguel Syjuco and Beauty Is a Wound (2002, translated into English in 2015) by Eka Kurniawan challenge this paradigm through diegetic play and political irreverence. They employ postmodernist strategies in parodying their national legacies – that of the Philippines and Indonesia respectively – and by doing so offer an effective means of re-engaging with the static narratives of history and nationalism. Although the parodic mode is not exclusive to the realm of the postmodernists, its execution through postmodernist narrative techniques legitimises parody as a meaningful form of cultural expression. Focusing on the aesthetic strategies of these novels works to overturn the regional homogenisation brought on by colonialism; at the same time, this focus coheres political history with literary theory innovatively. By choosing their national histories as the targets of their jokes, Ilustrado and Beauty Is a Wound urgently present the redemptive possibilities of postmodernist fiction and parody to reconceptualise the past in order to renew meanings in the present.